3D/4D spatiotemporal image correlation (STIC) fetal echocardiography provides incremental benefit over 2D fetal echocardiography in predicting postnatal surgical approach in double‐outlet right ventricle. (11th February 2021) - Karmegaraj, B.; Kumar, S.; Srimurugan, B.; Sudhakar, A.; Simpson, J. M.; Vaidyanathan, B.
ABSTRACT: Objective: To analyze the incremental benefit of 3D/4D spatiotemporal image correlation (STIC) fetal echocardiography over 2D fetal echocardiography with respect to the accuracy of identification of anatomic details crucial for surgical decision‐making and in predicting surgical approach in fetuses with double‐outlet right ventricle (DORV). Methods: This was a retrospective study of fetuses with DORV which had undergone both 2D echocardiography and 3D/4D STIC echocardiography and which underwent surgery postnatally in a tertiary pediatric cardiac center in Kerala between October 2015 and March 2019. All such cases with normal atrial arrangement, concordant atrioventricular connections and balanced ventricles were included. 2D and 3D/4D STIC fetal echocardiographic data were analyzed by two experienced observers blinded to the other dataset. Anatomic variables crucial for surgical decision‐making, i.e. location and routability of the ventricular septal defect, relationship of the great arteries and presence of outflow obstruction, were compared between the two modalities with respect to agreement with postnatal echocardiography. The accuracy of prenatal prediction of the surgical pathway was compared between 2D and 3D/4D modalities with respect to the procedure undertaken. Results: Included in the study were 22 fetuses with DORV which had undergone both 2D and 3D/4D imaging as well as postnatal surgery. Accuracy of prenatal interpretation of all four anatomic variables was significantly higher using 3D/4D STIC than using 2D fetal echocardiography (19/22 (86.4%) vs 8/22 (36.4%), P  < 0.001). Surgical procedures included single‐stage repair in 14 (63.5%) patients and a multistage approach in eight (36.4%). Prenatal prediction of the surgical pathway was significantly more accurate on 3D/4D STIC than on 2D echocardiography (20/22 (90.9%) vs 12/22 (54.5%), P  = 0.021). Prenatal predictive accuracy of single‐stage biventricular repair was significantly better for 3D/4D STIC than for 2D echocardiography (14/14 (100%) vs 8/14 (57.1%), P  = 0.04). Conclusion: Addition of 3D/4D STIC to conventional 2D fetal echocardiography confers incremental benefit on the accuracy of identification of anatomic details crucial for surgical decision‐making and the prediction of postnatal surgical approach in fetuses with DORV, thereby potentially aiding prenatal counseling. © 2020 International Society of Ultrasound in Obstetrics and Gynecology.